Symbol rate estimation of PSK signal based on PLL and wavelet transform - Nan XIA; Tian-shuang QIU; Jing-chun LI (Tongxin xuebao)
An improved algorithm for symbol rate estimation based on wavelet transform was proposed.The PLL based phase adaptive tracking approach was applied to synchronize the phase between the receiver and the itter and extract the signal envelope.The symbol rate was estimated from the wavelet transform magnitudes of the base-band signal.The improved algorithm effectively solved the problem on the result of estimation suffering from initial phases and noise occurred in the classical Chan’s algorithm.Simulation results verify that the novel algorithm is efficient and superior to the existing algorithms.